Fraction Activities Rosella Flower (Hibiscus Sabdariffa L) as an Antibacterial and Antibiofilm Escherichia Coli ATCC 25922 - Ratna Ika Yusuf; Ana Indrayati; Ismi Rahmawati (Jurnal Multidisiplin Madani, 2024)
Rosella flowers (Hibiscus sabdariffa L) contain alkaloid, flavonoid, saponin and tannin compounds. The compounds contained in rosella flowers have activity as antibacterial and antibiofilm. Biofilm is the ability of microorganisms that stick to the surface of objects and form a matrix. This study aims to antibacterial and biofilm activity in the form of inhibition of biofilm formation and biofilm degradation of E.coli bacteria. Rosella flowers were extracted using maceration method with 96% ethanol solvent. The thick extract was then fractionated with n-hexane, ethyl acetate and water solvents. Antibacterial activity test using diffusion and dilution methods followed by observation of cell wall and membrane damage using SEM and ion leakage with AAS. Biofilm activity test was conducted using a microplate device and readings were taken at a wavelength of 595 nm. The absorbance results of the inhibition percentage to determine the IC50 and EC50 values. The average IC50 values of biofilm formation inhibition test on extract, n-hexane fraction, ethyl acetate fraction and water fraction against E. coli bacteria are 1.059; 1.070; 0.921; 0.863. The EC50 values of biofilm degradation test on extract, n-hexane fraction, ethyl The minimum killing concentration value of rosella flower water fraction against E. coli is 25 mg/ml. the effect of the active fraction of rosella flower on E. coli bacteria is on the cell wall and cell membrane